2020
DOI: 10.3390/publications8030043
|View full text |Cite
|
Sign up to set email alerts
|

Research Contribution of the Oldest Seat of Higher Learning in Pakistan: A Bibliometric Analysis of University of the Punjab

Abstract: Bibliometric methods are used to access various elements in any data set. Similarly, this study uses a bibliometric method to evaluate the research performance of the University of the Punjab (PU), the oldest university of Pakistan. A peer university from a neighboring country, India, has been selected in this study along with three state-owned universities of Pakistan. The research yield of selected universities was analyzed since their establishment until 2019. The data were retrieved from the Scopus databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 37 publications
2
16
0
Order By: Relevance
“…It has also been applied to large-scale studies to explore publishing trends and dynamics regarding research in countries and regions (Ahmed et al , 2021; Ul Haq et al , 2020). Furthermore, some researchers have used bibliometric methods to measure the research productivity of institutions (Ahmad et al , 2020a, 2020b) and journals (Haq et al , 2021). We have used the term “Arab World” for the regional block of 22 Arab countries which are members of the Arab League (Algeria, Bahrain, Comoros, Djibouti, Egypt, Iraq, Jordan, Kuwait, Lebanon, Libya, Mauritania, Morocco, Oman, Palestine, Qatar, Saudi Arabia, Somalia, Sudan, Syria, Tunisia, United Arab Emirates and Yemen).…”
Section: Methodsmentioning
confidence: 99%
“…It has also been applied to large-scale studies to explore publishing trends and dynamics regarding research in countries and regions (Ahmed et al , 2021; Ul Haq et al , 2020). Furthermore, some researchers have used bibliometric methods to measure the research productivity of institutions (Ahmad et al , 2020a, 2020b) and journals (Haq et al , 2021). We have used the term “Arab World” for the regional block of 22 Arab countries which are members of the Arab League (Algeria, Bahrain, Comoros, Djibouti, Egypt, Iraq, Jordan, Kuwait, Lebanon, Libya, Mauritania, Morocco, Oman, Palestine, Qatar, Saudi Arabia, Somalia, Sudan, Syria, Tunisia, United Arab Emirates and Yemen).…”
Section: Methodsmentioning
confidence: 99%
“…The current study also adds that the number of authors is positively correlated with citations. Previously Pakistani studies confirmed this positive association between the number of authors and research impact (Iqbal et al , 2018; Ahmad et al , 2020; Haq, 2020).…”
Section: Guidelines For Academic Policy-making and Gap Analysismentioning
confidence: 65%
“…Pakistani researchers are producing more in the discipline of Science and Technology, e.g. chemistry (Ahmad et al , 2020) and Pharmacology (Latif and Haq, 2020). Also, in Pakistan, in science and technology, multiple authorship trends are witnessed, e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[61] conducted a bibliometric study on security and application of bibliometric, while [62] conducted a bibliometric study for how security is analyzed in the blockchain. There are few studies about security such as [63][64][65][66][67] analyzed the security issues using bibliometric studies and extracted the major publication patterns. MFA is not a new research area, but the real usage came with a number of security issues on a rise.…”
Section: Introductionmentioning
confidence: 99%